Game-Based Learning: Teaching May Require Fun (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
This article advocates for using game-based learning in the classroom. Some topics are difficult to teach because they require an entirely different mindset. Studies show that game-based learning can provide a new structure of learning to teach these new skills. Research from around the world demonstrates that using games in the classroom allows students to stretch to a new kind of thinking that improves their performance on assessments and their ability to think at higher levels. Particular attention must paid to game selection, which should focus on learning objectives. When no pre-made game fits the lesson, teachers can design their own games. Another focus must be the post-game discussion, in which the teacher can connect the activity to the core material.